Rehabilitation and Strengthening of Damaged Reinforced Concrete Beams Using Carbon Fiber-Reinforced Polymer Laminates and High-Strength Concrete Integrating Recycled Tire Steel Fiber - Hasan A. Alasmari; Ibrahim A. Sharaky; Ahmed S. Elamary; Ayman El-Zohairy (Fibers)
Currently, millions of tires are consumed annually, which necessitates the efficient disposal of these quantities of spent tires and the development of means to convert them into useful materials. This research deals with the effect of adding the steel fibers extracted from used car tires (RSFs) to incorporate them as concrete components to obtain high-strength concrete (HSC). The HSC was used in this paper to strengthen the pre-damaged beams by jacking. In the first phase, twelve beams were subjected to an overload equal to 80% of their total expected bearing capacity to obtain damaged RC beams, while one beam was loaded to failure (reference beam, RB0). In the second phase, the damaged beams were strengthened with HSC jacketing integrating RSFs with three contents (0, 0.25, and 0.5%) or by HSC jacking and bonded CFRP laminates to the bottom surface of the jacket. Moreover, the Abaqus finite element (FE) program was implemented to simulate the upgraded damaged beams. The result ensured enhanced HSC compressive and tensile strengths by 11.6–14.4% and 11.6–20.9% as the RSF % increased from 0 to 0.25 and 0.5%, respectively. Using the HSC jacket with 0, 0.25, and 0.5% RSF to strengthen the RC-damaged beams increased the load capacity by 8.8, 14.5, and 20.1%, respectively compared to RB0. Furthermore, strengthening the damaged RC beams with both HSC jacket and CFRP laminates enhanced their load capacity by 41.9, 45.5, and 50.3% as the HSC integrated 0, 0.25, and 0.5% RSF, respectively, compared to RB0. Finally, the FE model could reveal several aspects related to the behavior of the damaged beams strengthened with jackets and CFRP laminates and the interaction between the different beam components.